Hubungan Putri Tanjung Sebagai Influencer dengan Brand Awareness Program “Ngobrol Sore Semaunya” - Marshelia; Alexander, Billy; Setiawan, Albert Octavio (Universitas Islam Balitar, 2023)
The more technology develops, the more a company's marketing strategy will develop, for example, influencers use. Ngobrol Sore Semaunya (NSS) is CXO Media's brand that presents content by exploring the inspiring stories of a famous figure. NSS's host is Putri Tanjung, and she is a presidential special staff, entrepreneur, and influencer. Therefore, this study aims to examine the strength of the relationship and the significance of the relationship between Putri Tanjung as an influencer and NSS' brand awareness. The theory used in this study is a two-step flow of communication, and the method used is quantitative by distributing questionnaires. The population of this study is 25,000 followers of NSS's Instagram. The sample is 100 people, which is selected through simple random sampling. The result showed a high relationship with positive direction relation between Putri Tanjung as an influencer and NSS brand awareness.